2022
DOI: 10.1128/msystems.00632-22
|View full text |Cite
|
Sign up to set email alerts
|

Long-Read Metagenome-Assembled Genomes Improve Identification of Novel Complete Biosynthetic Gene Clusters in a Complex Microbial Activated Sludge Ecosystem

Abstract: Cataloguing secondary metabolite (SM) potential using genome mining of metagenomic data has become the method of choice in bioprospecting for novel compounds. However, accurate biosynthetic gene cluster (BGC) detection requires unfragmented genomic assemblies, which have been technically difficult to obtain from metagenomes until very recently with new long-read technologies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 74 publications
1
17
0
Order By: Relevance
“…Specifically, when BGCs are located on contig edges, their count can be artificially increased when analyzed with antiSMASH as a broken BGC is likely to be counted twice. Thus the number of BGCs on the contig edge is a metric of genome quality for BGC analysis [23]. We identified only 6,524 BGCs (9.2%) situated at contig edges indicating a high quality of the collected dataset at capturing mostly complete BGCs [24].…”
Section: Resultsmentioning
confidence: 99%
“…Specifically, when BGCs are located on contig edges, their count can be artificially increased when analyzed with antiSMASH as a broken BGC is likely to be counted twice. Thus the number of BGCs on the contig edge is a metric of genome quality for BGC analysis [23]. We identified only 6,524 BGCs (9.2%) situated at contig edges indicating a high quality of the collected dataset at capturing mostly complete BGCs [24].…”
Section: Resultsmentioning
confidence: 99%
“…[Kitasatospora] papulosa (10) Streptomyces longwoodensis (10) Streptomyces cellulosae (12) Streptomyces virginiae (12) Streptomyces canus (17) Streptomyces albidoflavus (19) Streptomyces anulatus (31) Other Streptomyces (476)…”
Section: Data Availabilitymentioning
confidence: 99%
“…These features have established genome mining as a complementary approach to the bioactivity and compound-centered discovery of novel bioactive molecules 8 . As some of these BGCs, such as the gargantulide BGC 9 , have sizes of more than 200 kbp, high quality genome assemblies have a strong influence on the quality of the genome mining analyses, as contiguous sequence data allows the identification of complete gene clusters and not just fragments – a challenge that is prevalent with low to medium quality draft genome and many metagenomic datasets 10 .…”
Section: Introductionmentioning
confidence: 99%

A treasure trove of 1,034 actinomycete genomes

Jørgensen,
Mohite,
Sterndorff
et al. 2024
Preprint
Self Cite
“…BGCs are the genes encoding secondary metabolites (SMs), a cluster of bacterium-originated chemical compounds with bioactivities and diverse structures. As the bridge between microbiome and host, BGCs have proven to be associated with diseases [95] , [96] . Jaeyun Sung et al utilized TaxiBGC on gut microbiome samples from three published case-control studies and found 5 BGCs elevated in CD patients, which encoded for gassericin E, gassericin S, gassericin T, acticin Q and ruminococcin A, respectively [95] .…”
Section: Gut Microbiome In CDmentioning
confidence: 99%